2011
DOI: 10.1093/jac/dkr357
|View full text |Cite
|
Sign up to set email alerts
|

Liver toxicity associated with antiretroviral therapy including efavirenz or ritonavir-boosted protease inhibitors in a cohort of HIV/hepatitis C virus co-infected patients

Abstract: The frequency of grade 3-4 TEs associated with efavirenz-based ART combinations under clinical practice conditions is low and similar to that found in patients receiving PI/r currently used in HIV/HCV co-infected patients. The baseline fibrosis stage does not have an impact on the development of TEs caused by these antiretroviral drugs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
2
25
0
1
Order By: Relevance
“…The observed cholestasis liver injury was more of transient and mild. The low severity grade of efavirenz based HAART is accordance with other reports [35]. Though mild in most patients, efavirenz based HAART induced liver injury can be life threatening in susceptible individuals [13].…”
Section: Discussionsupporting
confidence: 90%
“…The observed cholestasis liver injury was more of transient and mild. The low severity grade of efavirenz based HAART is accordance with other reports [35]. Though mild in most patients, efavirenz based HAART induced liver injury can be life threatening in susceptible individuals [13].…”
Section: Discussionsupporting
confidence: 90%
“…assessed the frequency of severe LEEs among 76 Spanish patients initiating an efavirenz-containing regimen and 186 initiating a boosted PI. (24) There was no difference in the proportion developing grade 3–4 LEEs between the two groups (efavirenz, 6.6%; boosted PI, 8.1%, P=0.681). Indeed, in two recent reviews of the hepatotoxicity of ARVs among all HIV-infected patients (25) and among HIV/HCV-coinfected individuals (26), the hepatic safety profile of newer agents appears significantly improved compared to agents used in the late 1990s and early 2000s.…”
Section: Discussionmentioning
confidence: 79%
“…Several other studies also reported the same conclusion. 19e22 Neukam et al 19 and Pineda et al 21,22 found no association between underlying advanced liver fibrosis and occurrence of TE in different HAART regimens, including NNRTI and boosted PI. Prospective studies with longer follow-up periods and a larger population size should be conducted to confirm the relationship between liver fibrosis and TE frequency in HIV and HCV co-infected patients.…”
Section: Discussionmentioning
confidence: 99%